Integron Mediated Multiple Heavy Metal and Antibiotic Resistance in Plant Growth Promoting Epiphytic Bacteria - Noor-e-Saba; Rida Batool; Nazia Jamil (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The present study was conducted to investigate the co-selection of antibiotic and heavy metal resistance in epiphytic bacteria isolated from Withania somnifera, Ficus benghalensis, Olea europaea and Aloe vera. Thirty epiphytic bacterial strains were isolated. Six isolated strains were selected and observed to have significant multiple heavy metals and antibiotics resistance. Single and synergistic effect of heavy metals and antibiotics constantly boosted the growth rate of selected bacterial isolates. Inoculation of these epiphytic bacteria caused increment in seedling, shoot and root length upto 58-70%, 25-37%, 87-125% respectively, while there was an increase in number of leaves upto 25-50% of Triticum aestivum. These epiphytic bacteria exhibited high extracellular antioxidant potential with rise in DPPH (2, 2-diphenyl 1-picrylhydrazyl) scavenging ability (33-59%) and phenols concentration (78-173 µg/ml). Phylogenetic analysis revealed 99-100% similarity of these bacterial strain AN1 (Staphylococcus pasteuri), AN2 (Microbacterium paraoxydans), BG4 (Pseudomonas azotoformans), BG6 (Staphylococcus haemolyticus), OL21 (Staphylococcus haemolyticus), and AV2 (Paenobacillus lactis). Sixty-six percent of these bacteria carried IntI1 gene having similarity with XerC integrase/recombinases superfamily conserved domains. Our findings suggested that existence of IntI1 gene in epiphytic bacterial genome helps in their survival under stress environment.